Adversity in pastoral leadership Are pastors leaving the ministry in record numbers, and if so, why? - Elkington, Robert (2013)
As churches in the West grapple with the rising tide of secularism, post-modernism and individualised spirituality, the leaders of those churches become casualties of these macro-environmental factors. Statistics show that three pastors in North America leave the vocational ministry every day to move into a different career path. This ongoing loss of leadership must prove detrimental for churches, which in turn are confronting declining attendance figures, declining income and low volunteerism from the membership. It would seem that pastoral leadership is vital to the health and sustenance of the church, and yet churches all over North America are losing pastoral leadership on a daily basis. This article attempts, through the use of Osmer’s heuristic, to review why it is that pastors are leaving the ministry and what might be done to stem that tide. A missional ontology in contrast to a Christendom ontology together with a review of workplace adversity and the Scriptural data on suffering in the ministry are developed for the reader as potential solutions to stem the tide.
Keywords: adversity; Leadership; pastoral attrition; pastoral burnout; pastoral leadership